Synthesis and characterization of North Aceh CEC bentonite determination with methylene blue method and increased D-Spacing after addition of surfactants CTAB-SDS - Siregar, J. P.; Jamiluddin, Jaafar; Teuku, Rihayat; Suryani; Satriananda; M., Yunus; Sariadi; Fitria; Shafira, Riskina; Zuhra, Amalia; Wildan, Syahputra; Nurhanifa; et al. (IOP Publishing Ltd, 2019)
Bentonite is not susceptible to polymers because it is organophilic and has low basal spacing. The main objective of this study is to increase bason spacing of bentonite and change the properties of bentonite to hydrophobic by modifying bentonite with cationic and anionic surfactants using Cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS). Surfactant with different CEC concentration, namely CTAB 1 CEC, 2 CEC and 3 CEC while SDS 0.5 CEC, 1 CEC and 1.5 CEC where the CEC is generated by halometric methods. From the results of the analysis with CEC bentonite value through the halometric method obtained 95.2 meq/ 100 grams clay, while the basal spacing of interlayer bentonite with modification of cationic and anionic surfactants using X-Ray Diffraction (XRD) obtained an increase in basal spacing from 14. 18393 Å to 25.08971 Å on CTAB 3 CEC and SDS 1.5 CEC. This research can produce bentonite from northern Aceh with the largest basal spacing so that it can be intercalated by other additives.